2018
DOI: 10.1161/jaha.118.008609
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Impact of a Chronic Total Coronary Occlusion on Ventricular Arrhythmias and Long‐Term Mortality in Patients With Ischemic Cardiomyopathy and an Implantable Cardioverter‐Defibrillator (the eCTOpy‐in‐ICD Study)

Abstract: BackgroundPrevious studies report conflicting results about a higher incidence of ventricular arrhythmias in patients with a chronic total coronary occlusion (CTO). We aimed to investigate this association in a large cohort of implantable cardioverter defibrillator patients with long‐term follow‐up.Methods and ResultsAll consecutive patients from 1992 onwards who underwent implantable cardioverter defibrillator implantation for ischemic cardiomyopathy at the Leiden University Medical Center were evaluated. Cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…Also, the eCTOpy‐in‐ICD study showed that patients with an ICD for ischemic cardiomyopathy (ICM) with a concurrent CTO received more appropriate device therapy and had a higher all‐cause mortality, compared with ICD patients with ICM without a CTO. Accordingly, in this study a suggestion of electrical stabilization after successful revascularization of a CTO was observed 26 . Interestingly, a previous study has demonstrated higher rates of ventricular ectopy during exercise in patient who underwent SPCI compared to FPCI 27 .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Also, the eCTOpy‐in‐ICD study showed that patients with an ICD for ischemic cardiomyopathy (ICM) with a concurrent CTO received more appropriate device therapy and had a higher all‐cause mortality, compared with ICD patients with ICM without a CTO. Accordingly, in this study a suggestion of electrical stabilization after successful revascularization of a CTO was observed 26 . Interestingly, a previous study has demonstrated higher rates of ventricular ectopy during exercise in patient who underwent SPCI compared to FPCI 27 .…”
Section: Discussionsupporting
confidence: 55%
“…Accordingly, in this study a suggestion of electrical stabilization after successful revascularization of a CTO was observed. 26 Interestingly, a previous study has demonstrated higher rates of ventricular ectopy during exercise in patient who underwent SPCI compared to FPCI. 27 Thus, although previous research indicates an association between arrhythmogenesis and CTOs, the extent to which FPCI affects arrhythmogenesis remains hard to define.…”
Section: Ecg Parametersmentioning
confidence: 96%
“…The recovering hibernating cardiomyocytes and ion channels in the revascularized CTO‐area could become overstimulated and therefore be more prone for VE than untreated hibernating myocardium. The eCTOpy‐in‐ICD study, investigating ICD‐therapy in CTO patients, shows that revascularization of the CTO is associated with reduction of appropriate ICD‐therapy rates for VT and VF on the long‐term, suggesting that CTO PCI might eventually, but not early on, lead to stabilization of the electrical vulnerability . Given these apparently disparate findings between the current study and the eCTOpy‐in‐ICD study further research is warranted to investigate whether revascularization of a CTO leads to electrical reactivation of the hibernating CTO area, which could initially induce proarrhythmogenicity but has a stabilizing effect in the long‐run.…”
Section: Discussionmentioning
confidence: 73%
“…(b). QTc-duration during the exercise test per randomization group CTO is associated with reduction of appropriate ICD-therapy rates for VT and VF on the long-term, suggesting that CTO PCI might eventually, but not early on, lead to stabilization of the electrical vulnerability 22.…”
mentioning
confidence: 99%
“…Among patients with CTO, renal dysfunction and LVEF <40% were independent factors associated with appropriate ICD therapy. Van Dongen et al evaluated 722 patients with ischemic cardiomyopathy who received an ICD for primary and secondary prevention [33]. A CTO was an independent predictor of appropriate ICD therapy.…”
Section: Cto In Icd Recipientsmentioning
confidence: 99%